Robotics Modelling, Planning and Control - Siciliano, Bruno. (Advanced Textbooks in Control and Signal Processing,, 2009)
The classic text on robot manipulators now covers visual control, motion planning and mobile robots too! Robotics provides the basic know-how on the foundations of robotics: modelling, planning and control. The text develops around a core of consistent and rigorous formalism with fundamental and technological material giving rise naturally and with gradually increasing difficulty to more advanced considerations. The theory of manipulator structures presented in the early part of the book encompasses: " the fundamentals: kinematics, statics and trajectory planning; and " the technology of actuators, sensors and control units. Subsequently, more advanced instruction is given in: " dynamics and motion control of robot manipulators; " environmental interaction using exteroceptive sensory data (force and vision); " mobile robots; and " motion planning. Appendices ensure that students will have access to a consistent level of background in basic areas such as rigid-body mechanics, feedback control, and others. Problems are raised and the proper tools established to find engineering-oriented solutions rather than to focus on abstruse theoretical methodology. To impart practical skill, more than 60 examples and case studies are carefully worked out and interwoven through the text, with frequent resort to simulation. In addition, nearly 150 end-of-chapter problems are proposed, and the book is accompanied by a pdf solutions manual and MATLABʼ code for computer problems; these are available free of charge to those adopting Robotics as a textbook for courses. This text is suitable for use in senior undergraduate and graduate courses in automation and computer, electrical, electronic and mechanical engineering courses with strong robotics content.